High-strength and high-toughness aluminum-neodymium alloy target material as well as preparation method and application thereof
By adding a variety of elements and phosphorus doped graphite alkyne to the aluminum-neodymium alloy, complex precipitation phases and compounds are formed, and the problems of protrusion, high resistivity and high brittleness in the high-temperature process of Al-Nd alloy targets are solved, and aluminium-neodymium alloy targets with high strength, high toughness and excellent electrical properties are achieved.
Patent Information
- Application Number
- CN202510024353.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
AI Technical Summary
The existing Al-Nd alloy targets are prone to protruding problems in high-temperature processes, resulting in a decrease in film quality and performance. At the same time, high neodymium content will increase resistivity and affect conductivity. The alloy itself is brittle and prone to fracture.
By adding Nd, Cu, Mg, Ti, Sr and phosphorus doped graphiteyne to the aluminum neodymium alloy, complex intermetallic compounds and precipitation phases are formed, which hinders dislocation movement, refines grains, and improves the strength, toughness and electrical properties of the alloy.
The strength, toughness and high temperature resistance of aluminum-neodymium alloy targets are significantly improved, brittle fracture is avoided, resistivity is reduced, and conductive performance is improved.
Smart Images

Figure BDA0005232310430000121 
Figure BDA0005232310430000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloys, and in particular relates to a high-strength and high-toughness aluminum-neodymium alloy target material and a preparation method and application thereof. Background Art
[0002] Alloy target is a key material used as an atomic or molecular source in coating processes such as physical vapor deposition (PVD) and chemical vapor deposition (CVD). It is made of two or more metals, or metal and non-metal elements, through smelting, sintering and other processes, based on aluminum and adding other elements. For example, Al-Nd alloy target, when the Nd content is ≥3wt%, can resist the formation of harmful hemispherical hillocks during heating, and has little effect on electronic resistivity, which is suitable for large-size TFT-LCD panels. Although Al-Nd alloy target improves the heat resistance of aluminum to a certain extent, when the process temperature exceeds its tolerance range, problems such as protrusions may still occur, affecting the quality and performance of the film. At process temperatures above 350°C, a higher content of neodymium is required to avoid protrusions, but this will increase the resistivity of the film and cannot meet the requirements of actual applications. As the neodymium content increases, the conductivity of the alloy decreases, which is unfavorable for some application scenarios with high requirements for conductive properties. For example, in the preparation of the electrode layer of electronic devices, excessively high resistivity may cause problems such as signal transmission delay and increased power consumption. In addition, the Al-Nd alloy itself may have a certain degree of brittleness and is prone to brittle fracture when subjected to external impact or thermal stress.
[0003] For example, CN103184419A discloses a method for producing an aluminum-neodymium alloy target material, which comprises: (1) cutting an aluminum ingot and a metal neodymium block into thin strips, ultrasonically cleaning the surface, drying, weighing and loading into a furnace, evacuating the furnace body, heating an alumina crucible to 800-1000°C, performing vacuum medium-frequency induction melting, shutting down the power supply, casting the ingot with a copper water-cooled mold, cooling the ingot with the furnace, and breaking the vacuum to take out the ingot; (2) performing high-temperature casting stress elimination and component homogenization annealing treatment, and then performing surface turning and peeling of the aluminum-neodymium alloy ingot and cutting off shrinkage holes at the head; (3) heating to 350-600°C for hot forging until the alloy thickness is 15-30 mm; (4) heating to 350-500°C and rolling treatment, with the rolling pass deformation rate being 10%-30%; (5) performing stress relief annealing; and (6) machining. This application uses a variety of processes to make the resulting aluminum-neodymium alloy target material have high density and uniform grain size distribution, but the toughness and strength of the resulting alloy target material still need to be improved.
[0004] For example, CN104152765A discloses a magnesium-lithium-aluminum-neodymium alloy, which is composed of the following components by mass: Li: 8.97-9.36%; Al: 3.2-3.45%; Nd: 0.4-2.75%; unavoidable impurities ≤ 0.3%; the rest is magnesium; the magnesium alloy is prepared by the following method: first, raw materials are selected according to a ratio and mixed and smelted to obtain an alloy melt; then the alloy melt is water-cooled to obtain a cast magnesium alloy; then the cast magnesium alloy is heated to 250-300°C and kept warm for 8-10 hours; and finally, the finished product is extruded. The present invention adds a certain amount of rare earth Nd to the Mg-Li alloy. During smelting, Nd is enriched before the solid-liquid interface, resulting in component supercooling, which inhibits grain growth and refines the grains. The application further adds an appropriate amount of Al to the alloy. During the smelting process, Al and Nd form Al2Nd and Al11Nd3 compound phases with high melting points and high thermal stability. During the hot working process, the phases pin grain boundaries and dislocations, hinder the growth of dynamically recrystallized grains, and further refine the grains. However, the electrical conductivity of the alloy in the application still needs to be improved.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a high-strength and high-toughness aluminum-neodymium alloy target material and a preparation method and application thereof. The aluminum-neodymium alloy target material provided by the present invention has excellent strength and toughness, and its electrical properties are excellent.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] In the first aspect, an embodiment of the present invention provides a high-strength and high-toughness aluminum-neodymium alloy target, comprising the following components by weight: Nd: 1.67%-4.56%; Cu: 1.45%-2.58%; Mg: 3.12%-5.16%; Ti: 3.23%-5.34%; Sr: 2.45%-4.12%; phosphorus-doped graphyne: 6.56%-8.56; the balance is Al.
[0009] In a preferred embodiment, the alloy target comprises the following components by weight: Nd: 2.5%-4.0%; Cu: 1.8%-2.4%; Mg: 3.5%-5.0%; Ti: 3.8%-5.0%; Sr: 2.8%-4.0%; P-doped graphyne: 7%-8; and the balance is Al.
[0010] The present invention effectively improves the strength, toughness and high temperature resistance of the alloy by compounding multiple elements, and avoids the brittleness of the alloy itself causing brittle fracture when subjected to external impact or thermal stress.
[0011] Specifically, in terms of improving strength, Nd, Cu, Mg, and Ti will form Al 11 Nd3, Al2Cu, Al 12 Mg 17 , Al3Ti and other intermetallic compounds. These tiny and dispersed second phase particles become obstacles to the movement of dislocations when the alloy is deformed, making it difficult for dislocations to slip, greatly increasing the external force required for plastic deformation, and thus synergistically strengthening the strength of the alloy. That is, when the compounded elements of the present invention exist at the same time, the aging precipitation process affects each other to form a more complex and smaller precipitated phase, and the strengthening effect far exceeds that of a single element. In addition, Cu, Mg, and Sr elements will partially dissolve into the aluminum matrix to form a solid solution, causing varying degrees of lattice distortion. The distorted areas caused by multiple elements are intertwined with each other, and the hindering effect on dislocations is much stronger than that of a single element, just like setting more and more complex roadblocks on an originally smooth road, making it more difficult for dislocations to move, and the strength of the alloy increases accordingly.
[0012] In terms of improving toughness, Nd, Ti, and Sr are all excellent grain refiners. Nd atoms segregate at the solidification front to hinder grain growth; Ti can form heterogeneous nucleation cores such as TiAl3; Sr changes the atomic diffusion mechanism in the aluminum liquid to promote nucleation. The three work together to greatly reduce the grain size of aluminum alloys and significantly increase the grain boundary area. Fine grains make the crack propagation path tortuous and changeable, and crack propagation requires more energy, which improves toughness. Mg has good ductility. When an appropriate amount of Mg is dissolved in the alloy, it can undergo local plastic deformation when subjected to stress, relieve stress concentration, and avoid premature crack initiation. At the same time, the grain structure refined by other elements provides more channels for stress dispersion. The two complement each other to maintain the toughness of the alloy.
[0013] In terms of improving high temperature resistance, Nd and Ti compounds are highly stable and not easy to decompose at high temperatures. They are distributed at grain boundaries and within grains, firmly locking the grain boundaries like solder joints, inhibiting grain boundary slip and grain growth, and maintaining the stability of the alloy structure. The precipitated phases formed by Cu and Mg elements can still hinder dislocation movement at higher temperatures, and the multi-phase synergy slows down the attenuation of the mechanical properties of the alloy under high temperature conditions. In addition, Mg and Sr elements tend to form a dense oxide film on the surface of the alloy. In a high-temperature aerobic environment, this film isolates oxygen, slows down further oxidation inside the alloy, prevents performance degradation due to oxidation degradation, and helps improve the high temperature resistance of the alloy.
[0014] In a preferred embodiment, the specific preparation method of the phosphorus-doped graphyne is as follows:
[0015] S1, passing acetylene gas into cuprous chloride ammonium solution, filtering, washing and drying after reaction to obtain a solid phase, mixing the solid phase, hexabromobenzene, tetrakis(triphenylphosphine)palladium and toluene and reacting, washing and drying after reaction to obtain a precursor, heating the precursor under nitrogen protection to obtain graphyne;
[0016] S2, mixing graphyne with phosphoric acid, and then reacting them in an argon atmosphere. After the reaction is completed, cooling, washing, drying, grinding and sieving are performed to obtain phosphorus-doped graphyne.
[0017] In a preferred embodiment, in step S1, the mass ratio of the solid phase, hexabromobenzene, tetrakis(triphenylphosphine)palladium and toluene is 1:(0.4-1.3):(0.4-1.1):(15-40).
[0018] In a preferred embodiment, in step S1, the reaction conditions are: reflux reaction at 40-100°C for 24-72h, and then concentration to dryness at 50°C-90°C.
[0019] In a preferred embodiment, in step S1, the heating reaction conditions are: temperature 300°C-600°C, time 24-36h.
[0020] In a preferred embodiment, in step S2, the mass ratio of graphyne to phosphoric acid is 1:(50-100).
[0021] In a preferred embodiment, in step S2, the reaction conditions are: calcination at 400-800° C. for 2-4 h.
[0022] In a preferred embodiment, in step S2, the sieve used for screening is 200-400 mesh.
[0023] The present invention improves the dispersion performance of graphyne itself in the alloy through self-made phosphorus-doped graphyne, and synergistically improves the electrical properties of the alloy with other elements, especially solves the problem that the electrical conductivity of the alloy is reduced due to the Nd content being greater than 3% in the alloy, and further synergistically improves the strength, toughness and high temperature resistance of the alloy with other elements.
[0024] Specifically, phosphorus-doped graphyne usually has a nanoscale size, which is smaller than the grain size of the alloy matrix. According to the Hall-Page equation, grain refinement can improve the strength and toughness of the material. Nano-sized phosphorus-doped graphyne is equivalent to a fine dispersed phase in the alloy, which can effectively hinder the movement of dislocations, while also increasing the phase interface area, making the stress distribution in the alloy more uniform, thereby improving the overall performance of the alloy.
[0025] Moreover, the doping of phosphorus atoms will introduce certain defects and active sites into the carbon skeleton of Graphyne. During the alloy preparation process, these active sites can react chemically with certain elements in the alloy to form chemical bonds. In the present invention, phosphorus atoms may react with elements such as aluminum and titanium in the alloy to generate metal phosphides. These metal phosphides can serve as a bridge to closely connect phosphorus-doped Graphyne with the alloy matrix, thereby improving its dispersion stability in the alloy. In addition, phosphorus doping can change the surface chemical properties of Graphyne and reduce its surface energy. After the surface energy is reduced, the agglomeration tendency of phosphorus-doped Graphyne in the alloy is weakened, and it is easier to be evenly dispersed in the alloy matrix. At the same time, the lower surface energy is also conducive to the wetting between it and the alloy matrix, so that phosphorus-doped Graphyne can be better integrated into the alloy, further improving the dispersibility. It is further explained that the magnesium element specially added in the present invention has a higher diffusion rate in the aluminum alloy, which can preferentially diffuse to the surrounding of phosphorus-doped Graphyne during the solidification process of the alloy, reduce the interface energy between Graphyne and the alloy matrix, thereby promoting the uniform dispersion of Graphyne in the alloy. Furthermore, in the present invention, phosphorus-doped graphyne and copper elements will form second phases such as Cu3P, which are uniformly distributed in the alloy and can serve as pinning points for phosphorus-doped graphyne, limiting its agglomeration and migration in the alloy, thereby improving its dispersibility.
[0026] In terms of improving electrical properties, Cu is an excellent conductor, and dissolving aluminum improves electrical conductivity. Phosphorus-doped graphyne has unique electrical properties. The defects introduced by phosphorus doping can provide more transmission channels for carriers and improve mobility. The combination of the two optimizes the alloy carrier concentration and mobility and enhances electrical conductivity. In addition, grain refinement and uniform dispersion of phosphorus-doped graphyne reduce scattering centers such as grain boundaries and impurities, making electron transmission smoother, reducing resistivity, and improving electrical properties.
[0027] In terms of improving strength, Nd, Cu, and Ti can form various intermetallic compounds with aluminum, such as Nd generating Al11Nd3, Cu generating Al2Cu, and Ti forming Al3Ti. These fine second phases are dispersed in the alloy and hinder dislocation movement. The lamellar structure of phosphorus-doped graphyne also has a barrier effect. The multi-phase synergy increases the dislocation slip resistance and strengthens the alloy. During aging treatment, Cu and Ti precipitate phases cooperate with phosphorus-doped graphyne to increase the strength far beyond the addition of a single element. While Cu and Mg partially dissolve into the aluminum matrix to cause lattice distortion, the phosphorus atoms of phosphorus-doped graphyne will also change the local electron cloud distribution. The complex distortion caused by the alloying elements greatly increases the difficulty of dislocation movement and improves the strength of the alloy.
[0028] In terms of improving toughness, Nd, Ti, and Sr are powerful grain refiners, which promote the refinement of aluminum grains and the increase of grain boundaries. The two-dimensional flexible structure of phosphorus-doped graphyne can absorb energy through deformation and peeling when cracks propagate, making the crack propagation path tortuous, combining many fine grains, buffering crack propagation, avoiding brittle fracture, and maintaining toughness. The good ductility of Mg enables it to undergo local plastic deformation when subjected to stress, alleviating stress concentration. Phosphorus-doped graphyne can also rely on its own flexibility to disperse stress and synergistically ensure the toughness of the alloy.
[0029] In a second aspect, an embodiment of the present invention provides a method for preparing a high-strength and high-toughness aluminum-neodymium alloy target as described above, comprising the following steps:
[0030] Nd powder, Cu powder, Mg powder, Ti powder, Sr powder, phosphorus-doped graphyne powder and Al powder are ball-milled in an argon atmosphere and then sieved. The mixed powder is then fed into a spray gun, and the powder is sprayed onto the surface of a target base tube using the spray gun to obtain an alloy target.
[0031] In a preferred embodiment, the ball milling conditions are: adding 2-4 wt% ethanol to the raw material powder, and ball milling at 500-800 rpm for 30-60 min.
[0032] In a preferred embodiment, the sieve used for screening is 200-400 mesh.
[0033] In the present invention, the various components are mixed evenly by adding ethanol, and in particular, phosphorus-doped graphyne is dispersed in the alloy powder, thereby ensuring that the electrical properties of the alloy target material are uniform.
[0034] Specifically, phosphorus-doped graphyne has a certain hydrophobicity and poor affinity with alloy powder, and is easy to agglomerate in the early stage of ball milling. Ethanol is a polar organic solvent with low surface tension, which can spread on the surface of phosphorus-doped graphyne, reduce the surface energy difference between it and the alloy powder, and make graphyne easier to contact with alloy powder particles, rather than adsorbing and agglomerating with each other. And ethanol molecules will adsorb on the surface of phosphorus-doped graphyne to form a solvation layer. This solvation layer has a certain charge or steric hindrance effect, which makes the graphyne particles repel each other, prevents them from reagglomerating due to van der Waals forces, and is conducive to its dispersion in the alloy powder. And during ball milling, the impact force of the grinding ball is the key to breaking the agglomerates and promoting dispersion. As a liquid medium, ethanol can more effectively transmit the impact force of the grinding ball to the agglomerates of phosphorus-doped graphyne, making it more evenly stressed and easier to be broken into single or smaller agglomerates, and then dispersed in the alloy powder. When phosphorus-doped graphyne particles collide with alloy powder particles or grinding balls, ethanol acts as a buffer to reduce excessive crushing or cold welding between particles caused by rigid collision. It makes the collision process softer, allowing phosphorus-doped graphyne to gradually and evenly disperse in the alloy powder system under continuous force, rather than abnormal aggregation due to excessive local force. Furthermore, during the ball milling process, friction and collision between powder particles will generate static electricity, and electrostatic adsorption often causes phosphorus-doped graphyne and alloy powder to agglomerate separately. Ethanol contains hydroxyl groups and is a polar molecule that can be adsorbed on the surface of powder particles with static electricity, neutralize part of the charge, and rely on its own dielectric properties to shield the electrostatic field, weaken the promotion of static electricity on particle agglomeration, and assist in the uniform dispersion of phosphorus-doped graphyne.
[0035] In a third aspect, the present invention provides a use of the high-strength and high-toughness aluminum-neodymium alloy target material as described above in the preparation of a conductive layer or a barrier layer.
[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0037] 1. The present invention effectively improves the strength, toughness, and high temperature resistance of the alloy by compounding multiple elements, thereby avoiding the brittleness of the alloy itself which causes brittle fracture when subjected to external impact or thermal stress.
[0038] 2. The present invention improves the dispersion performance of graphyne itself in the alloy through self-made phosphorus-doped graphyne, and synergistically improves the electrical properties of the alloy with other elements, especially solves the problem that the Nd content in the alloy is greater than 3%, which leads to a decrease in the electrical conductivity of the alloy, and further synergistically improves the strength, toughness and high temperature resistance of the alloy with other elements.
[0039] 3. In the present invention, the various components are mixed evenly by adding ethanol, and in particular, phosphorus-doped graphyne is dispersed in the alloy powder, thereby ensuring that the electrical properties of the alloy target are uniform. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available.
[0042] Nd powder, purity 99.5wt.%, particle size D50=8μm, purchased from Zibo Rongruida Powder Material Factory;
[0043] Cu powder, purity 99.8wt.%, particle size -200 mesh, purchased from Tianjin Bohai Welding Materials Co., Ltd.;
[0044] Mg powder, purity 99.8wt.%, particle size -325 mesh, purchased from Shandong Baiweida New Materials Co., Ltd.
[0045] Ti powder, purity 99.5wt.%, particle size -200 mesh, purchased from Beijing Xingrongyuan Technology Co., Ltd.;
[0046] Sr powder, purity 99.5wt.%, particle size D50=5μm, purchased from Shanghai Naio Nano Technology Co., Ltd.;
[0047] Al powder, purity 99.8wt.%, particle size -325 mesh, purchased from Beijing Xingrongyuan Technology Co., Ltd.
[0048] Example 1
[0049] This embodiment provides a method for preparing a high-strength and high-toughness aluminum-neodymium alloy target, comprising the following steps:
[0050] By mass, 3 parts of Nd powder, 2 parts of Cu powder, 4 parts of Mg powder, 4 parts of Ti powder, 3 parts of Sr powder, 7 parts of phosphorus-doped graphyne powder and 77 parts of Al powder were ball-milled in an argon atmosphere and then passed through a 200-mesh sieve. The ball-milling conditions were as follows: 3 wt % ethanol was added to the raw material powder, and the mixture was ball-milled at 600 rpm for 40 minutes. The mixed powder was then fed into a spray gun, and the powder was sprayed onto the surface of the target base tube using the spray gun to obtain an alloy target.
[0051] The specific preparation method of phosphorus-doped graphyne is as follows:
[0052] S1, by mass, acetylene gas is introduced into a cuprous chloride ammonium solution, after the reaction, the solid phase is obtained by filtering, washing and drying, 1 part of the solid phase, 0.6 parts of hexabromobenzene, 0.6 parts of tetrakis(triphenylphosphine)palladium and 25 parts of toluene are mixed and refluxed at 80°C for 30 hours, and then concentrated to dryness at 70°C, followed by washing and drying to obtain a precursor, and the precursor is heated at 500°C for 28 hours under nitrogen protection to obtain graphyne;
[0053] S2, by mass, 1 part of graphyne was mixed with 70 parts of phosphoric acid, and then calcined at 550°C for 3 h in a tube furnace under an argon atmosphere. After the reaction was completed, the mixture was cooled, washed, dried, and ground through a 200-mesh sieve to obtain phosphorus-doped graphyne.
[0054] Example 2
[0055] This embodiment provides a method for preparing a high-strength and high-toughness aluminum-neodymium alloy target, comprising the following steps:
[0056] By mass, 3.8 parts of Nd powder, 2.2 parts of Cu powder, 4.5 parts of Mg powder, 4.5 parts of Ti powder, 3.5 parts of Sr powder, 7.8 parts of phosphorus-doped graphyne powder and 73.7 parts of Al powder were ball-milled in an argon atmosphere and then passed through a 200-mesh sieve. The ball-milling conditions were as follows: 3 wt % ethanol was added to the raw material powder, and the mixture was ball-milled at 600 rpm for 40 minutes. The mixed powder was then fed into a spray gun, and the powder was sprayed onto the surface of the target base tube using the spray gun to obtain an alloy target.
[0057] The specific preparation method of phosphorus-doped graphyne is as follows:
[0058] S1, by mass, acetylene gas is introduced into a cuprous chloride ammonium solution, after the reaction, the solid phase is obtained by filtering, washing and drying, 1 part of the solid phase, 0.6 parts of hexabromobenzene, 0.6 parts of tetrakis(triphenylphosphine)palladium and 25 parts of toluene are mixed and refluxed at 80°C for 30 hours, and then concentrated to dryness at 70°C, followed by washing and drying to obtain a precursor, and the precursor is heated at 500°C for 28 hours under nitrogen protection to obtain graphyne;
[0059] S2, by mass, 1 part of graphyne was mixed with 70 parts of phosphoric acid, and then calcined at 550°C for 3 h in a tube furnace under an argon atmosphere. After the reaction was completed, the mixture was cooled, washed, dried, and ground through a 200-mesh sieve to obtain phosphorus-doped graphyne.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that 3 parts of Nd powder are replaced by 1 part of Nd powder, and 77 parts of Al powder are replaced by 79 parts of Al powder.
[0062] Comparative Example 2
[0063] The difference between this comparative example and Example 1 is that no Nd powder is added, and 77 parts of Al powder are replaced by 80 parts of Al powder.
[0064] Comparative Example 3
[0065] The difference between this comparative example and Example 1 is that no Cu powder is added, and 77 parts of Al powder are replaced by 79 parts of Al powder.
[0066] Comparative Example 4
[0067] The difference between this comparative example and Example 1 is that no Mg powder is added, and 77 parts of Al powder are replaced by 81 parts of Al powder.
[0068] Comparative Example 5
[0069] The difference between this comparative example and Example 1 is that Ti powder is not added, and 77 parts of Al powder are replaced by 81 parts of Al powder.
[0070] Comparative Example 6
[0071] The difference between this comparative example and Example 1 is that Sr powder is not added, and 77 parts of Al powder are replaced by 80 parts of Al powder.
[0072] Comparative Example 7
[0073] The difference between this comparative example and Example 1 is that phosphorus-doped graphyne powder is not added, and 77 parts of Al powder are replaced by 84 parts of Al powder.
[0074] Comparative Example 8
[0075] The difference between this comparative example and Example 1 is that 7 parts of phosphorus-doped graphyne powder are replaced with 7 parts of graphyne powder.
[0076] Performance Testing
[0077] 1. The finished alloy target materials obtained in the above embodiments and comparative examples were subjected to coating experiments to test the sputtering performance of the target materials. The substrate was a hard alloy (WC-8% Co) with a specification of 10×10×8 mm. After grinding, mirror polishing, ultrasonic cleaning, and hot air drying, it was ready for use.
[0078] Select the same coating experimental parameters: background vacuum degree 5×10 -4 Pa, the substrate was heated to 500 °C, and then filled with pure N2 at a pressure of 3.5 Pa, a substrate bias of -100 V, and a power density of 17 W / cm 2 The deposition time was adjusted to obtain a coating with a thickness of about 3 μm. The sputtering performance of the target is shown in Table 1.
[0079] Among them, the discharge stabilization time refers to the empty burning time, that is, the time the target material is empty sputtered before it meets the requirements of depositing thin films (the discharge frequency reaches a certain value). The longer the discharge stabilization time, the more defects such as pores, inclusions, and non-conductive oxides inside the target material, and the poorer the uniformity of the phase and organization. The shorter the discharge stabilization time, the higher the density of the target material and the better the organization uniformity.
[0080] The surface roughness of the coating is measured using a surface profiler or atomic force microscope.
[0081] The hardness of the coating was measured using a microhardness tester with a load of 0.05 kgf.
[0082] Table 1 Target sputtering performance test results
[0083] Discharge stabilization time / min Coating roughness / nm <![CDATA[Hardness / HV 0.05 > Example 1 28 76 3057 Example 2 32 83 3123 Comparative Example 1 24 69 3028 Comparative Example 2 22 64 2971 Comparative Example 3 23 65 2965 Comparative Example 4 25 63 3011 Comparative Example 5 21 62 3014 Comparative Example 6 20 61 2993 Comparative Example 7 15 54 2876 Comparative Example 8 17 58 2908
[0084] Table 2 Target mechanical and high temperature test results
[0085]
[0086]
[0087] It can be seen from the above performance test results that the electrical properties, strength, toughness and high temperature resistance of Examples 1-2 are significantly improved, especially the comprehensive performance of Example 2 is the most outstanding. This is mainly because the synergistic effect between the various elements compounded in the present invention and rare earth oxides and phosphorus-doped graphyne effectively improves the electrical properties, strength, toughness and high temperature resistance of the alloy target.
[0088] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. This better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.
[0089] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength and high-toughness aluminum-neodymium alloy target, characterized in that: The invention comprises the following components by weight: Nd: 1.67%-4.56%; Cu: 1.45%-2.58%; Mg: 3.12%-5.16%; Ti: 3.23%-5.34%; Sr: 2.45%-4.12%; phosphorus-doped graphyne: 6.56%-8.56; and the balance is Al.
2. The high-strength and high-toughness aluminum-neodymium alloy target according to claim 1, characterized in that: The alloy target material comprises the following components by weight: Nd: 2.5%-4.0%; Cu: 1.8%-2.4%; Mg: 3.5%-5.0%; Ti: 3.8%-5.0%; Sr: 2.8%-4.0%; P-doped graphyne: 7%-8; the balance is Al.
3. The high-strength and high-toughness aluminum-neodymium alloy target according to claim 1 or 2, characterized in that: The specific preparation method of the phosphorus-doped graphyne is as follows: S1, passing acetylene gas into cuprous chloride ammonium solution, filtering, washing and drying after reaction to obtain a solid phase, mixing the solid phase, hexabromobenzene, tetrakis(triphenylphosphine)palladium and toluene and reacting, washing and drying after reaction to obtain a precursor, heating the precursor under nitrogen protection to obtain graphyne; S2, mixing graphyne with phosphoric acid, and then reacting them in an argon atmosphere. After the reaction is completed, cooling, washing, drying, grinding and sieving are performed to obtain phosphorus-doped graphyne.
4. The high-strength and high-toughness aluminum-neodymium alloy target according to claim 3, characterized in that: In step S1, the mass ratio of the solid phase, hexabromobenzene, tetrakis(triphenylphosphine)palladium and toluene is 1:(0.4-1.3):(0.4-1.1):(15-40).
5. The high-strength and high-toughness aluminum-neodymium alloy target according to claim 3, characterized in that: In step S1, the reaction conditions are: reflux reaction at 40-100° C. for 24-72 hours, and then concentration to dryness at 50° C.-90° C.; And / or, in step S1, the heating reaction conditions are: temperature 300°C-600°C, time 24-36h.
6. The high-strength and high-toughness aluminum-neodymium alloy target according to claim 3, characterized in that: In step S2, the mass ratio of graphyne to phosphoric acid is 1:(50-100).
7. The high-strength and high-toughness aluminum-neodymium alloy target according to claim 3, characterized in that: In step S2, the reaction conditions are: calcining at 400-800°C for 2-4h; And / or, in step S2, the sieve used for screening is 200-400 mesh.
8. A method for preparing a high-strength and high-toughness aluminum-neodymium alloy target as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: Nd powder, Cu powder, Mg powder, Ti powder, Sr powder, phosphorus-doped graphyne powder and Al powder are ball-milled in an argon atmosphere and then sieved. The mixed powder is then fed into a spray gun, and the powder is sprayed onto the surface of a target base tube using the spray gun to obtain an alloy target.
9. The method for preparing a high-strength and high-toughness aluminum-neodymium alloy target according to claim 8, characterized in that: The ball milling conditions are as follows: adding 2-4 wt% ethanol to the raw material powder and ball milling at 500-800 rpm for 30-60 min; And / or, the sieve used for the sieving is 200-400 meshes.
10. Use of the high-strength and high-toughness aluminum-neodymium alloy target material as claimed in any one of claims 1 to 8 in preparing a conductive layer or a barrier layer.
Citation Information
Patent Citations
Production method of aluminum-neodymium alloy target material
CN103184419A
Magnesium-lithium-aluminum-neodymium alloy
CN104152765A